Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern [i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi [ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann).
Keywords: Inklusion; Kooperation; Eltern; Sekundarstufe 1; Evaluation; Integration; Schulentwicklung; Elternkooperation

Evaluation Criteria in Product Idea Selection Decisions - Gräßler, Iris; Koch, Anna-Sophie (XXXIII Proceedings of the ISPIM Innovation Conference)
Within innovation management, choosing the best fitting product idea is the most important decision point. The future existence and success of the organization is depending on selected product ideas. To find the best fitting idea for an organization, it needs evaluation criteria representing the organizations mission Therefore, this study focuses on a holistic overview about evaluation criteria and on supporting organizations in the process to select its individual evaluation criteria. Based on a literature study, existing approaches regarding evaluation criteria in product idea selection are identified and a list of evaluation criteria is reworked. Using the list of evaluation criteria, a prioritization method is created. Within an interview with experts in innovation management, the method is discussed regarding usability and the level of assistance in product idea selection. The developed criteria can be used directly by innovation manager and industrial practitioners to evaluate potential product ideas.
Keywords: innovation management; evaluation criteria; idea selection; idea evaluation; meta-study

Experimental Measurement Method and Evaluation of an Analytical Approach for Sound Conduction through Multiple Clinched Sheets - Stephan, Richard; Brosius, Alexander (The 28th Saxon Conference on Forming Technology SFU and the 7th International Conference on Accuracy in Forming Technology ICAFT)
The conduction of structure-borne sound through joints causes energy dissipation. The sound reduction index describes this energy loss as a level decrease in the particle velocity across series-connected damping elements for which the superposition principle applies. This simple model can help to develop a testing method for joints based on this characteristic energy loss. In this paper, this model is experimentally evaluated for multiple in-series clinched aluminium sheets. Samples connected by several clinch points arranged in parallel are investigated experimentally, and the results are discussed.
Keywords: clinching; mechanical joining; damping; model; evaluation; dynamics

Evaluation eines digitalen Fachspezifischen Chinesischsprachkurses für Studierende des Ingenieurwesens - Hambach, Dennis (die hochschullehre. Interdisziplinäre Zeitschrift für Hochschule und Lehre)
Ziel dieser Studie ist es den digitalen moodlegestützten asynchronen Sprachkurs Fachspezifisches Chinesisch für das „Maschinenbau in China Programm“ (mb-cn) der Fakultät für Maschinenbau der Universität Paderborn zu evaluieren, um Handlungsempfehlungen für zukünftig ähnlich aufgebaute Projekte zu entwickeln. Dazu wurden im Sommersemester 2021 sechs leitfadengestützte Interviews geführt. Die Interviews wurden anschließend mithilfe von deduktiv ermittelten Kategorien, die sich aus dem Technology Acceptance Model 2 (TAM2) nach Venkatesh und Davis (2000) ergaben, nach Mayring (2015) analysiert, um abschließend die Forschungsfrage zu beantworten: „Wie bewerten mb-cn Ingenieurstudierende die wahrgenommene Nützlichkeit der digitalen Sprachlernangebote des Kurses Fachspezifisches Chinesisch?“.
Keywords: Technology Acceptance Model; Fachspezifische Chinesischsprachkurse; digitale Lehre; Moodle; Evaluation

Supporting Innovation Management for SMEs: A Tool for Idea Selection - Gräßler, Iris; Koch, Anna-Sophie; Thiele, Henrik; Dattner, Michael (Proceedings of the ISPIM Innovation Conference)
In innovation management, usually there is a large number of product ideas, not all of which meet the requirements of a company and make sense to pursue further. For selecting the most promising ideas, several methods exist which each focus on a certain aspect. Due to the characteristics of Small and Medium Enterprises (SMEs) such as limited resources, these enterprises have special requirements on methods for selecting ideas. In this study, criteria of SMEs for idea selection are deducted from SME-characteristics. Methods for idea selection are tested for fulfillment of these criteria and the results are combined in a matrix. Together with a guideline, a tool for idea selection in innovation management of SMEs is developed. The results are validated in the context of innovation management in SMEs. By selecting a method, a SME is enabled to make economically viable decisions for their product portfolio, thus ensuring sustainable economic success.
Keywords: innovation management; SME; evaluation method; idea selection; meta-study; idea evaluation

Qualitative and Quantitative Analysis of Callgraph Algorithms for PYTHON - Kummita, Sriteja; Piskachev, Goran; Spaeth, Johannes; Bodden, Eric (Proceedings of the 2021 International Conference on Code Quality (ICCQ))
As one of the most popular programming languages, PYTHON has become a relevant target language for static analysis tools. The primary data structure for performing an inter-procedural static analysis is call-graph (CG), which links call sites to potential call targets in a program. There exists multiple algorithms for constructing callgraphs, tailored to specific languages. However, comparatively few implementations target PYTHON. Moreover, there is still lack of empirical evidence as to how these few algorithms perform in terms of precision and recall. This paper thus presents EVAL_CG, an extensible framework for comparative analysis of Python call-graphs. We conducted two experiments which run the CG algorithms on different Python programming constructs and real-world applications. In both experiments, we evaluate three CG generation frameworks namely, Code2flow, Pyan, and Wala. We record precision, recall, and running time, and identify sources of unsoundness of each framework. Our evaluation shows that none of the current CG construction frameworks produce a sound CG. Moreover, the static CGs contain many spurious edges. Code2flow is also comparatively slow. Hence, further research is needed to support CG generation for Python programs.
Keywords: Static Analysis; Callgraph Analysis; Python; Qualitative Analysis; Quantitative Analysis; Empirical Evaluation

The Debate on student evaluations of teaching: global convergence confronts higher education traditions - Pineda, Pedro; Steinhardt, Isabel (Teaching in Higher Education)
Through co-occurrence analysis of 1139 documents (1964-2018) we identified trends in the discussions about the implementation of student teaching evaluation (SET). We found that: (1) Attention to SET originated in the US in the 1970s, spreading to German-speaking countries in the mid-1990s and continuing in China and Latin America in the early 2000s. (2) SET is commonly viewed as a control tool deserving methodological improvement, while bias is debated in the US. We also found local trajectories: (3) Whereas in the US and Latin America SET is primarily seen as a management tool, German-speaking and Chinese authors reflect more on improving teaching. Chinese scholars consider SET a valid instrument for state control associated with artificial intelligence. Also, (4) SET is commonly used in medical education in the US and the German-speaking region and in physical education in China. We conclude that SET is discussed cross-nationally but affected by national path dependencies.
Keywords: academic discourse; bibliometric review; quality assurance; student evaluation of teaching; teaching evaluation

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

Das Praxissemester fachdidaktisch in den Blick nehmen - Wosnitza, Christopher; Caruso, Carina; Vogelsang, Christoph (die hochschullehre)
In vielen Bundesländern ist ein Praxissemester obligatorischer Bestandteil der Lehramtsausbildung. Zunehmend wird untersucht, ob und in welcher Form Studierende die für diesen Ausbildungsabschnitt vorgesehenen Standards erreichen. Dabei fokussieren Untersuchungen primär bildungswissenschaftliche Kompetenzbereiche. Die Frage, inwiefern das Praxissemester zum Erwerb domänenspezifischer bzw. insbesondere fachdidaktischer Kompetenzen beiträgt, lässt sich als Forschungsdesiderat konstatieren. Es ist zudem unklar, wie bestimmte Lerngelegenheiten diesen Prozess beeinflussen. Um diesem Forschungsbedarf zu begegnen, wurde an der Universität Paderborn die interdisziplinäre Forschungsgruppe Fachdidaktische Forschung im Praxissemester gegründet. Ziel der gemeinsamen Arbeit ist es, auf Basis wissenschaftlicher Ergebnisse einen Beitrag zur Weiterentwicklung des Praxissemesters zu leisten. Am Praxissemester sind drei Ausbildungsorte beteiligt: Hochschulen, Zentren für schulpraktische Lehrerausbildung (ZfsL) und Schulen. Ein Schwerpunkt liegt daher auf der Untersuchung des kritisch-produktiven Verhältnisses von Hochschullehre und Praxis. Vor dem Hintergrund fachübergreifender Heuristiken zur Professionalisierung in der Lehrer/innenbildung, werden in diesem Artikel aktuelle Projekte der Forschungsgruppe und deren Kontexte vorgestellt und diskutiert.
Keywords: Praxissemester; Lehrer/innenbildung; Evaluation; Kompetenzentwicklung; Fachdidaktik / school internships; teacher education; evaluation; professional competence; subject matter education

Zum Einfluss des didaktischen Designs auf das (motivationale) Erleben von Lehrveranstaltungen: Eine quantitative Fallstudie im Rahmen der Methodeneinführung in den Bildungswissenschaften - Goller, Michael (die hochschullehre)
Im Sinne eines Scholarship of Teaching and Learning wird in diesem Aufsatz die Neugestaltung einer eigenständig durchgeführten Lehrveranstaltung im Bereich der Forschungsmethoden empirisch untersucht. Die neugestaltete Lehrveranstaltung integriert sowohl direkt-instruktionale als auch kooperativ-offene Sitzungsformate und wird mit einer thematisch ähnlichen Lehrveranstaltung des Jahres 2012 verglichen, welche fast ausschließlich im Vorlesungsstil (direkt-instruktional) gehalten wurde. Im Mittelpunkt des Evaluationsvorhabens standen folgende Forschungsfragen: (1) Unterscheiden sich die summativen Evaluationen der Lehrveranstaltungen der Jahre 2012 und 2014 in den Variablen subjektiver Lernerfolg, Motivation zur selbstständigen Auseinandersetzung mit den Inhalten sowie Gesamteindruck des Seminars?, (2) Welchen Einfluss hat die Form der Sitzungsgestaltung (direkt-instruktional vs. kooperativ-offen) auf das Erleben von Kompetenz, Autonomie und sozialer Eingebundenheit?, (3) Welche Form der Sitzungsgestaltung wird von den Studierenden stärker akzeptiert? und (4) Welchen Einfluss hat die Form der Sitzungsgestaltung auf den subjektiven Lernerfolg der Studierenden? Empirisch zeigte sich, dass die neugestaltete Lehrveranstaltung des Jahres 2014 von den Studierenden in fast allen Variablen als lernwirksamer eingeschätzt wurde. Des Weiteren ergaben sich Hinweise, dass sich kooperativ-offene Sitzungsformate positiv auf motivationale Ausgangsbedingungen auswirken.
Keywords: Direkte Instruktion; Evaluation; Kooperatives Lernen; Methodenausbildung; Paderborn; Scholarship of Teaching and Learning

Encouraging Family and Parent Education: Program Development and Evaluation in the Federal State of Baden-Württemberg, Germany - Landhäußer, Sandra; Faas, Stefan; Treptow, Rainer (Center for Educational Policy Studies Journal (CEPS))
Against the background of a European-wide strategy of governance aimed at improving support for parents and families, the following report details the conceptualization and evaluation of a federal state program4 in Baden- Württemberg (Germany) which was launched in 2008 to encourage fam- ily and parent education. Two program components, a voucher system for parents with a new-born child and an element that emphasizes educa- tional offers for families with special needs in particular living situations, were started to increase requests for educational courses. The aim was to establish and deepen cooperation between different public and private professional services that are in contact with parents and their children. The results show that main goals of the program were reached.
Keywords: family and parent education; cooperation; voucher system; support for families with special needs in particular living situations; program evaluation

The reverb challenge: a common evaluation framework for dereverberation and recognition of reverberant speech - Kinoshita, Keisuke; Delcroix, Marc; Yoshioka, Takuya; Nakatani, Tomohiro; Habets, Emanuel; Haeb-Umbach, Reinhold; Leutnant, Volker; Sehr, Armin; Kellermann, Walter; Maas, Roland; Gannot, Sharon; Raj, Bhiksha (IEEE Workshop on Applications of Signal Processing to Audio and Acoustics)
Recently, substantial progress has been made in the field of reverberant speech signal processing, including both single- and multichannel de-reverberation techniques, and automatic speech recognition (ASR) techniques robust to reverberation. To evaluate state-of-the-art algorithms and obtain new insights regarding potential future research directions, we propose a common evaluation framework including datasets, tasks, and evaluation metrics for both speech enhancement and ASR techniques. The proposed framework will be used as a common basis for the REVERB (REverberant Voice Enhancement and Recognition Benchmark) challenge. This paper describes the rationale behind the challenge, and provides a detailed description of the evaluation framework and benchmark results.
Keywords: Reverberant speech; dereverberation; ASR; evaluation; challenge

A decision-theoretic foundation of IS business value research - Schryen, Guido; Bodenstein, Christian (Proceedings of the 18th European Conference on Information Systems (ECIS 2010))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. Three research tasks are essential requisites on the path towards addressing this criticism: the synthesis of knowledge, the identification of lack of knowledge, and the proposition of paths for closing knowledge gaps. This paper considers each of these tasks by a) synthesizing key research findings based on a comprehensive literature review, b) identifying and unfolding key limitations of current research, and c) applying a decision-theoretic perspective, which opens new horizons to IS business value research and shows paths for overcoming the limitations. The adoption of this perspective results in a decision-theoretic foundation of IS business value research and includes the proposition of a consistent terminology and a research model that frames further research.
Keywords: Decision theory; IT value; IS assessment; IS evaluation

Verlässlichkeitorientierte Technologiebewertung innovativer Aktortechnologien am Beispiel von Formgedächtnislegierungen - Müller, Thomas; Schiedeck, Florian; Hemsel, Tobias (2. Tagung des DVM -- Arbeitskreis Zuverlässigkeit mechatronischer und adaptronischer Systeme: Absicherung der Systemzuverlässigkeit, Koblenz)
EN: Although the use of new actuator technologies is quite enthusiastic, the realization of innovative systems based on these principles fails because of doubts in dependability. Until now, new working principles for actuators have not been systematically investigated in the means of dependability. Therefore we developed a proceeding for a dependability-oriented evaluation of technologies. This is shown in the case of shape memory alloy actuators. DE: Die Realisierung von Systemen mittels innovativer Aktortechnologien scheitert oftmals an der Skepsis gegenüber der Verlässlichkeit (Vertrauen in die zuverlässige und sichere Funktionalität der Technologie). Diese liegt darin begründet, dass neue Aktortechnologien bzw. die Integration von innovativen physikalischen Wirkprinzipen innerhalb neuer Aktorkonzepte bisher noch nicht systematisch im Kontext der Verlässlichkeit untersucht werden. Daher haben wir ein Vorgehen zur verlässlichkeitsorientierten Technologiebewertung entwickelt. Neben der detaillierten Darstellung des Vorgehensmodells wird es exemplarisch anhand von Formgedächtnislegierungen zur Entwicklung innovativer Antriebslösungen angewendet.
Keywords: EN: Dependability; Reliability; Evaluation of Technology; Actuators; Shape Memory Alloys DE: Verl{\